Pathways : changes in recruitment for child sexual abuse and life course events. - Alexander, Ryan (Kansas State University, 2011)
A major public concern is what to do with sex offenders. This seven-year study utilizes first-hand accounts from sex offenders who pursue children, exploring recruitment methods – that is, how they find and gain access to victims. Much public perception about sex offender recruitment is based on well-publicized cases such as that of Polly Klaas, Megan Kanka, and Jaycee Dugard – young girls who were abducted and, in the case of Klaas and Kanka, murdered, by strangers. Legislative efforts responded with laws such as “three strikes” and sex offender registries. Scientific studies have found such laws to be ineffective, yet heightened media exposure persists, perception of “stranger danger” prevails, and untried legislative initiatives continue. The most recent is “buffer zone” laws that limit where sex offenders live. To better inform perception and policy, this study investigates two samples of sex offenders concerning child recruitment. The first sample targeted a general population of sex offenders in state custody with a determinate sentence. The second focused on a population of sexually violent predators (SVP), as defined by Kansas law, constituting repeat offenders with a long history of sex offenses and/or those deemed legislatively as unfit for release into the community. The bulk of data came through interviews addressing activities that surrounded the offense(s), details of child recruitment, and, pertaining to the SVP sample, how offending corresponded with certain life events. Theoretically, the study is informed by Routine Activities Theory (RAT) and Life-Course Theory (LCT). RAT is based on a rational choice perspective of motivation and opportunity – an individualistic approach – while LCT sees offending episodes as strongly influenced by structural position. These two seemingly divergent theories represent a unique framework referred to here as conditioned activities, demonstrating how routine activities are altered by certain life events, or turning points, which, in turn, influence persistence or desistence in offending. It was discovered that child victim recruitment varies across the life course, specifically tied to changes in the offender’s social position. Age of the offender interacts with both position and life events.
Keywords: Sex offenders; Routine activities; Recruitment; Criminology (0627)